Stem-like T cells and niches: Implications in human health and disease - Yi, Linglu; Yang, Li (Frontiers in Immunology, 2022)
Recently, accumulating evidence has elucidated the important role of T cells with stem-like characteristics in long-term maintenance of T cell responses and better patient outcomes after immunotherapy. The fate of TSL cells has been correlated with many physiological and pathological human processes. In this review, we described present advances demonstrating that stem-like T (TSL) cells are central players in human health and disease. We interpreted the evolutionary characteristics, mechanism and functions of TSL cells. Moreover, we discuss the import role of distinct niches and how they affect the stemness of TSL cells. Furthermore, we also outlined currently available strategies to generate TSL cells and associated affecting factors. Moreover, we summarized implication of TSL cells in therapies in two areas: stemness enhancement for vaccines, ICB, and adoptive T cell therapies, and stemness disruption for autoimmune disorders.